Challenges of education in the accounting profession in the Era 5.0: A systematic review - Maria C. Tavares; Graça Azevedo; Rui P. Marques; Maria Anunciaç\~ao Bastos (Cogent Business & Management, 2023)
The significant transformations and advances attributed to the Era 5.0 require a comprehensive understanding of the current ramifications of the accounting discipline, along with the prospective difficulties and opportunities. This is pertinent not only in the context of industry, education, and society, but also in terms of labor relations and professions. Thus, the aim of this paper is to understand the current impacts and future expectations of the Era 5.0 on the accounting profession. Based on a recent systematic literature review we note the urgent and pressing need for educational institutions, their audiences, and other entities to interact in the changing process, creating synergies to ensure the success of retraining this valuable strategic resource in organizations and society, and the sustainability of the profession, promoting a sustainable Society 5.0. We contribute to the research on the consequences and challenges of the Era 5.0 in the future of the accounting profession by the originality of the contextualization of the profession in this new Era, filling a gap in the recent state of the art in the research of the accounting profession. We consider that this research will have an impact on academia, industry, and society, bringing these to work together in the development of the accountants' skills and their future work.
Keywords: 650; Accounting education; accounting professional; artificial intelligence; digital; Era 5.0; PICO; PRISMA; technologies